Pemanfaatan Barang Bekas Sebagai Sarana Pendidikan Nilai Infaq (Studi Kasus Yayasan A. Mappamadeng Mattiro Deceng Kabupaten Bone) - Siskawati, Siskawati; Ramadhani, Wulan; Hasbi, Hartas (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This study aims to analyze the system of collection, management, and utilization of used goods as a means of infak value education at the A. Mappamadeng Mattiro Deceng Foundation, Bone Regency. Used goods are collected from students to be processed into infak funds that are used for foundation purposes. This program aims to provide students with first-hand experience on the importance of sharing, while supporting the principle of sustainability by utilizing items that are considered waste into something of value. This program has a positive impact in increasing students' awareness of the importance of sharing and protecting the environment. In addition, this program also reflects the potential for integrating character education with sustainability issues through the management of used goods. This research provides recommendations to foundations to improve the efficiency of management and reporting systems, including the use of digital technology to support transparency and accountability. Thus, the results of this research can be a reference for other foundations that want to adopt similar programs as part of infak value education and environmental sustainability. In this study, we use descriptive qualitative methods with interview, observation, and document study methods. The research shows that the results of this program are effective in instilling the value of sharing and empathy in students. However, there are challenges in managing used goods and recording infak results. Recommendations are given to improve the reporting system and increase student engagement.